Application of technology for the design of transmedia projects in college: Case study: It ends with us - Fernández Manzano, Eva Patricia (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The term transmedia coined by Jenkins (2003) refers to those stories that expand their stories through different distribution channels. This way of building narrative stories becomes extremely interesting and natural for the Alpha and Zeta generation. Given this scenario, the university subject Creation of transmedia stories is presented as an opportunity for students to explore the possibilities of transmedia and apply it specifically to a cultural product. This article will analyze a cultural case study.